Characterizing severe obesity in children and youth referred for weight management - Salawi, Hebah A (BioMed Central, 2014)
BACKGROUND: Severe obesity (SO) in pediatrics has become increasing prevalent in recent decades. The objective of our study was to examine differences in demographic, anthropometric, cardiometabolic, and lifestyle variables in children and youth with SO versus their less overweight/obese (OW/OB) peers. METHODS: A retrospective medical record review of 6-19 year old participants enrolled in an outpatient pediatric weight management clinic was conducted. SO (body mass index [BMI] ≥99(th) percentile) and OW/OB (BMI ≥85(th) and <99(th) percentile) groups were created according to Centers for Disease Control and Prevention definitions. Demographic, anthropometric, cardiometabolic and lifestyle data reported at baseline (pre-intervention) were retrieved. RESULTS: Of the 345 participants, most were girls (56.2%), Caucasian (78.7%), and had family incomes > $50,000/year (65.7%). The SO group (n = 161) had lower HDL-cholesterol and higher liver enzymes, insulin resistance and blood pressure than the OW/OB group (n = 184; all p < 0.01). They also reported higher total energy intakes, fewer steps/day, less moderate-to-vigorous physical activity, and more leisure time screen time (all p < 0.02) than their leaner peers. Compared to the OW/OB group, a higher proportion of individuals in the SO group possessed cardiometabolic risk factors, including high triglycerides (45.8% vs 58.5%), alanine aminotransferase (55.4% vs 81.4%), insulin resistance (55.6% vs 82.1%), systolic blood pressure (11.5% vs 27.3%), diastolic blood pressure (17.8% vs 30.0%), and low HDL-cholesterol (44.6% vs 64.6%; all p < 0.02). Aside from the ~75% of participants (groups combined) who met the daily recommended intakes of grain and meat products, <50% of boys and girls met any of the remaining nutrition and physical activity-related recommendations. Compared to the OW/OB group, greater proportions of children and youth in the SO group failed to meet moderate-to-vigorous physical activity (48.4% vs 31.9%) and leisure-time-screen-time recommendations (43.4% vs 28.3%; both p < 0.05). CONCLUSION: Children and youth with SO have a worse cardiometabolic profile and less favorable lifestyle habits than their OW/OB peers. These differences emphasize the heightened obesity-related health risks associated with SO in the pediatric years.